PENGARUH PROPORSI KOMISARIS INDEPENDEN PADA NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Sunarwijaya Ketut (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
Independent commissioner is one of the corporate governance mechanism that affects the value of the company. While return on equity is a profitability ratio that is used to measure the financial performance of the company. This study uses a proxy profitability with a return on equity as an intervening variable. This study aims to determine the effect of indirect profitability in the relationship between the independent commissioner and the company’s value. This research was conducted in the Indonesia Stock Exchange in the financial year 2013-2015. The sampling method using purposive sampling techniques in order to obtain 120 samples of the study. Analysis of the data used in this research is descriptive statistics, classical assumption test and multiple linear regression analysis. The test results showed that the value of Adjusted R² of 0.770, F test has a significance value of 0.000, and the results of path analysis showed that the proportion of independent commissioner may be a direct effect on the value of the company and may also affect indirectly that is of the proportion of independent commissioner to profitability (as a variable intervening) and then to the value of the company. The amount of direct influence the proportion of independent commissioner on the company’s value is 0.234, while the amount of indirect influence of the proportion of independent commissioner on the company’s value through profitability is 0.410 while the total effect of the proportion of independent commissioners on a company value of 0.644.